Indonesian manuscripts in great Britain : a catolugue of manuscripts in Indonesia langiages in British public collections : naskah-naskah Indonesia di Inggris.... - Voorhoeve, M.C Ricklefs (Yayasan Obor, 2014)
xxix, 349 hlm.: 23 cm